Strength and conditioning practices for the optimisation of speed and accuracy in cricket fast bowlers: A systematic review and meta-analysis. Issue 5 (October 2022) - Ramachandran, Akhilesh Kumar; Singh, Utkarsh; Lathlean, Timothy JH
The most important determinants of a cricket fast bowler's performance are bowling speed and accuracy. Even though various strength and conditioning practices (resistance, plyometric and modified-implement training) have been employed to improve these parameters, there is still ambiguity as to the effectiveness of such training programmes. This systematic review and meta-analysis examined the influence of various training interventions on fast bowling speed and accuracy. Searches were conducted across PubMed, Web of science, SPORTDiscus, Scopus and CINAHL. Inclusion criteria were studies that: were original research or conference presentations; recruited fast bowlers as participants; involved a physical training intervention; written in English; and included bowling speed or accuracy as outcome measures. Ten articles met our inclusion criteria for qualitative and eight for quantitative analysis. The quality of the studies assessed using Downs and Black checklist ranged from low to moderate with a mean ± SD of 64.5 ± 8.14%. There was amoderate and significant effect of plyometric training intervention on bowling speed (SMD = 0.75; Z  = 2.98; p  = 0.003). Further, a small and non-significant effect of resistance training on bowling speed was observed in our study (SMD = 0.40; Z  = 1.39; p  = 0.164). A small but non-significant difference was found in the ball speed post modified ball weight training intervention (SMD = 0.30; Z  = 1.14; p  = 0.252). The findings from our study are useful for strength and conditioning coaches in helping to design and implement fast-bowling specific training programmes for improved bowling speed.